Improving life after stroke needs global efforts to implement evidence-based physical activity pathways. Issue 5 (July 2019) - van Wijck, Frederike; Bernhardt, Julie; Billinger, Sandra A; Bird, Marie-Louise; Eng, Janice; English, Coralie; Teixeira-Salmela, Luci Fuscaldi; MacKay-Lyons, Marilyn; Melifonwu, Rita; Sunnerhagen, Katharina S; Solomon, John M; Thilarajah, Shamala; et al.
There is an urgent need to improve life after stroke across the world—especially in low-income countries—through methods that are effective, equitable and sustainable. This paper highlights physical activity (PA) as a prime candidate for implementation. PA reduces modifiable risk factors for first and recurrent stroke and improves function and activity during rehabilitation and following discharge. Preliminary evidence also indicates PA is cost-effective. This compelling evidence urgently needs to be translated into seamless pathways to enable stroke survivors across the world to engage in a more active lifestyle. Although more quality research is needed—particularly on how to optimize uptake and maintenance of PA—this should not delay implementation of high-quality evidence already available. This paper shares examples of best practice service models from low-, middle-, and high-income countries around the world. The authors call for a concerted effort to implement high-quality PA services to improve life after stroke for all.